Fatty acid metabolism in gouty arthritis: mechanisms to therapeutic targeting - Zhao, Xueping; Sun, Ye; Yang, Le; Sun, Hui; Zhang, Xinya; Sun, Hui; Yan, Guangli; Wang, Xijun (Frontiers in Immunology, 2025)
Gouty arthritis (GA), a condition characterized by monosodium urate (MSU) crystal deposition and NLRP3 inflammasome-driven inflammation, is a result of a complex interplay between hyperuricemia and immune dysregulation, which leads to systemic complications and joint damage. Current therapies for GA exhibit certain limitations, including cardiovascular risks, hepatotoxicity, low efficacy in special populations, and difficulty in dissolving tophi. Emerging evidence implicates fatty acid metabolism disorders as key pathogenic factors in GA. Elevated fatty acids (FAs) activate Toll-like receptors (TLRs) in macrophages, which act in synergy with MSU crystals to trigger NLRP3 inflammasome activation and pro-inflammatory cytokine release (e.g., IL-1β), thereby initiating the inflammatory cascade. Dysregulated FA metabolism promotes neutrophil recruitment through aberrant arachidonic acid (AA) metabolism and exacerbates hyperuricemia by increasing purine synthesis while inhibiting uric acid excretion. Consequently, future clinical practice may leverage the detection of FA signatures in GA patients to enable tailored therapeutic and dietary management, thereby maximizing treatment efficacy while minimizing adverse effects. The combined application of FA-modulating agents and anti-GA therapeutics synergistically enhances therapeutic efficacy, enabling comprehensive disease-modifying control over GA progression. This review systematically elucidates the mechanisms through which FA metabolism disorders drive the progression of GA, providing a scientific basis for the subsequent research on GA.